2006
DOI: 10.1021/bi0525324
|View full text |Cite
|
Sign up to set email alerts
|

Translesion Synthesis Past Equine Estrogen-Derived 2‘-Deoxyadenosine DNA Adducts by Human DNA Polymerases η and κ

Abstract: Hormone replacement therapy (HRT) increases the risk of developing breast, ovarian and endometrial cancers. Equilin and equilenin are the major components of the widely prescribed drug used for HRT. 4-hydroxyequilenin (4-OHEN), a major metabolite of equilin and equilenin, promotes 4-OHEN-modified dC, dA, and dG DNA adducts. These DNA adducts were detected in breast tumor and adjacent normal tissues of several patients receiving HRT. We have recently found that 4-OHENdC DNA adduct is a highly miscoding lesion g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…The mechanism of forming DNA damage induced by equine estrogens (Bolton et al, 1998) and their mutagenic properties (Yasui et al, 2003; Suzuki et al, 2004; Yasui et al, 2006 & 2007) have been explored. However, the tumorigenic potential of equine estrogens has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of forming DNA damage induced by equine estrogens (Bolton et al, 1998) and their mutagenic properties (Yasui et al, 2003; Suzuki et al, 2004; Yasui et al, 2006 & 2007) have been explored. However, the tumorigenic potential of equine estrogens has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenic events induced by 4-OHEQ were observed in a supF shuttle vector plasmid propagated in human cells (Yasui et al, 2003). We have reported that the dC and dA adducts are frequently miscoded during DNA synthesis catalyzed by human DNA polymerases expressed highly in mammary tissue and reproductive organs (Suzuki et al, 2004; Yasui et al, 2006 & 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the bypass frequency in pol η differed by two orders of magnitude in the members of a pair of 4-OHEN-dC stereoisomers with opposite sign CD spectra (27). For 4-OHEN-dA adducts, the bypass frequency past one stereoisomer was approximately 3 times higher than for another (28). For a pair of 4-OHENdC major adducts whose CD spectra were opposite sign, with pol κ mismatched dCMP and dAMP were inserted opposite both stereoisomers, and chain extension with partner dC was much higher than with dA (27).…”
Section: Structure-function Relationshipsmentioning
confidence: 98%
“…Polymerases bypass the 4-OHEN-dC and dA lesions with efficiencies depending upon configuration and the identity of the damaged base [127–129]. Primer extension conducted with the polymerases Dpo4, Pol η , and Pol κ indicate that 4-OHEN-dC is bypassed with insertion of an incorrect dNTP or by strand slippage [128][130].…”
Section: Conformational Interconversions Of Dna Adductsmentioning
confidence: 99%